2008
DOI: 10.1111/j.1467-6443.2008.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fletcher Report 1930: A Historical Case Study of Contested Black Mixed Heritage Britishness

Abstract: This article examines a controversial report that focused negatively on mixed heritage children born and raised in the city of Liverpool. The official title was: Report on an Investigation into the Colour Problem in Liverpool and other ports. The social researcher was Muriel E. Fletcher, who had been trained in the Liverpool School of Social Science at The University of Liverpool in the early 1920s. The report was published in 1930 amid controversy for its openly stigmatizing content of children and mixed heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Her parents' status meant that her life was one of poverty on a London 'sink' council estate. Her Black-white 'mixed race' background was presented as a source of dysfunction and family trouble, a familiar theme borne of the UK's informal anti-miscegenation regime (Christian, 2008;Carby, 2007). Another part of her story is a familiar one for Black people as her lack of academic ability made her turn to her athletic capabilities, eventually becoming a fitness instructor and Olympic hopeful.…”
Section: Beyond Victim or Parody: Decolonizing Black Women's Bodiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Her parents' status meant that her life was one of poverty on a London 'sink' council estate. Her Black-white 'mixed race' background was presented as a source of dysfunction and family trouble, a familiar theme borne of the UK's informal anti-miscegenation regime (Christian, 2008;Carby, 2007). Another part of her story is a familiar one for Black people as her lack of academic ability made her turn to her athletic capabilities, eventually becoming a fitness instructor and Olympic hopeful.…”
Section: Beyond Victim or Parody: Decolonizing Black Women's Bodiesmentioning
confidence: 94%
“…Such racial ambiguity made her more palatable to a nation that still speaks of 'half castes'. 'Half caste', much like 'mixed race' and 'dual heritage' involve thinly veiled racial disgust of those who dare to mix or to be mixed (Gilroy, 2004;Christian, 2008;Carby, 2007). Racial disgust generates an atmosphere (Brennan, 2004;Gutíerrez Rodríguez, 2007 because of its intensity which means that disgust of racial mixing is never ambivalent about its object.…”
Section: Jessica Ennis: Fascination and Racial Brandingmentioning
confidence: 95%
“…It remained a racially diverse area with a high black population during the 20th century; by the 1970s Margaret Simey, a local councillor and chair of the Merseyside County Police Committee described Toxteth as a 'dumping ground' into which most working poor and Black residents of Liverpool were consigned to live (Nassy Brown, 2005: 68). The Liverpool-born Black population of Liverpool has consistently been marginalised through institutional racism and stereotypes, often excluded from Scouse identity (Christian, 2008;Boland, 2010).…”
Section: Pariah City: 3 Liverpool's Imagementioning
confidence: 99%
“…Toxteth is referred to in these examples using spatially fixed language such as a 'community just south of the city centre' and 'ghetto', both of which give a spatial fixity to Toxteth, but the difference and social distance is cast through references to the racial difference of Toxteth and its residents. This stranger-making is deeply ingrained in Liverpool with relation to the Liverpool-born Black community who have historically been marginalised and omitted from Scouse identity (Christian, 2008;Boland, 2010).…”
Section: Stranger-makingmentioning
confidence: 99%
“…Filled with racist and racialised assumptions, as Mark Christian observes, Fletcher's report can be seen as marking the official moment in defining Liverpool's 'half caste' children as a problem and blight to the 'British way of life' in Liverpool and other cities. 54 Fletcher concluded that in Liverpool white women who consorted with 'coloured men' fell into four main categories: women who needed a husband to care for an illegitimate child, those who were 'mentally weak', prostitutes, and 'younger women who make contacts in the spirit of adventure and are unable to break away'. 55 White women who claimed their 'coloured' partners to be good husbands Fletcher dismissed as women making excuses for their mistakes, for they 'almost invariably regret their alliance with a coloured man when they see they have chosen a life which is repugnant'.…”
Section: White Women and Their Families After 1914mentioning
confidence: 99%